Long term follow up of Endoscopic Injection Sclerotherapy with Absolute alcohol for Bleeding Esophageal Varices - Farooqi, Javed Iqbal; Hameed, Khalid; Ullah, Ikram; Khan, Ijaz M.; Shah, Sadiq (Journal of Postgraduate Medical Institute, 2011)
to investigate the long term cosnequences of endoscopic injection sclerotherapy using absolute alcohol as a sclerasing agents, 300 patients with bleeding esophageal varices were treated with injection sclerotherapy using absolute alcohol from january 1988 to december 1997, and were followed up to minimum of 30 months. The rate of complete eradication of esophageal varices was 95%. During the follow up period, the recurrence rate of varices was 28%; recurrence was noted between 10 and 20 months. The rates of recurrent bleeding adn death were 12% and 3%. We conclude that absolute alcohol is an ideal sclerosing agent for bleeding esophageal varices in our setup and is associated with low recurrence and mortality rates.